Effect of Rhizobacteria Promoting Plant Growth (PGPR) on Character of Resulting from Crossing Resiprocal Corn with Purple Waxy Corn with Sweet Corn (Zea mays L.) - Erny Ishartati; Mohammad Tri Setyawan; Indra Alfi Fadjri (Postgraduate, University of Mataram, 2022)
The purpose of this study was to obtain information about the good concentration of PGPR for the growth and yield of reciprocal crosses of purple waxy corn and sweet corn (Zea mays L.), the effect of PGPR on the character of a reciprocal cross between purple waxy corn and sweet corn (Zea mays L.) and the effect of reciprocal crosses of purple waxy corn with sweet corn (Zea mays L.) on the character of maize yield. The research was conducted in Tegalgondo Village, Karangploso District, Malang Regency, East Java Province. The study was arranged in a Split-Plot Design consisting of 4 main plots (PGPR Concentration) V0 (Without PGPR), V15 (15 ml PGPR / l water), V30 (30 ml PGPR / l water), V45 ( 45 ml of PGPR/ l of water) and consisted of 4 subplots (crosses) PW (Purple Waxy Maize), PWSC (Purple Waxy Corn♂ x Sweet Corn♀), SC (Sweet Corn) and SCPW (Sweet Corn♂ x Purple Pulut Corn). ). The data obtained were analyzed using the Analysis of Variance (ANOVA) at the 5% level. If there is a significant effect between treatments, it is continued with a comparison test with a 5% LSD test using Costad software and Microsoft Excel. Based on the results, it can be concluded that there is an interaction between the administration of PGPR and the reciprocal cross of purple waxy corn x sweet corn on the observation of sugar content characters. PGPR treatment with PGPR concentration of 45 ml/l water (V45) can increase growth and yield characteristics. The results of the reciprocal crosses (PWSC) of Purple Waxy Maize x Sweet Corn and (SCPW) Sweet Corn x Purple Waxy Maize showed that the female parents were more dominant than the male parents.